Interaksi Sosial Dosen dan Mahasiswa Pada Prodi TBI FITK - Susanti, Eka; Nasution, Nisa Fahria; Hamidiyah, Masita; Nst, Anggi Rahmanida; Afifah, Nabila Yun; Lubis, Rahma Fitri Yani; Srg, Aisyah Rizqa Fitri; Anwar, Hazril Fikri; Siahaan, Rizki Putri Jasmin (Yayasan Daarul Huda Kruengmane, 2024)
Interaction is the process by which people communicate and influence each other in thoughts and actions. Basically, humans in everyday life cannot be separated from their relationships with each other, where the behavior of each individual influences, changes or improves the behavior of other individuals or vice versa. In lectures, students must also have the ability to interact socially with lecturers. Student is the term for people who study at universities. A person can be called a student if he is active as a student and is registered at a university. Students are an intellectual community that better understands the problems that are occurring. Students have a role in analyzing problems that exist in society and then voicing them as aspirations to the government. As academics, students have the responsibility to implement the Tridharma of Higher Education. Students should be able to carry out academic tasks well and not rely on other people. Students have a role in society that needs to be maintained and strived to be achieved. Lecturers as student supervisors substantively play a role not only in teaching or transferring knowledge (cognitive), but are also required to be able to provide guidance and training. In Law no. 20 of 2003 concerning teachers and lecturers is confirmed in article 39 that; Apart from being tasked with carrying out administration, management, development and services in the Development Unit, lecturers are also professional staff tasked with planning and implementing processes and assessing learning outcomes, guidance and training. This research uses Research Method According to the researcher, a qualitative descriptive method is used in the name of research, which accurately understands the nature of field data and research objectives. Learn technical analysis techniques. The qualitative approach used by researchers is library research. Activities related to library data collection methods. According to Abdul Rahman Sholeh, library research is scientific research that uses methods to obtain information by searching library sites such as books, research papers, journals, historical reports, home research books, etc. Relating to pure goods. The research library has. From this research it can be concluded that the interactions that need to be fostered are interactions between lecturers and students as well as interactions between one student and another. As educators, lecturers must also be able to innovate in the learning process, especially in efforts to improve English speaking skills, namely by presenting interesting learning methods and techniques.